Determination of Bisphenol A in Paper Products by Synchronous Fluorescence Spectoscopy and Estimation of Daily Exposure - Gallimberti,Matheus (2020)
In this study, a simple and fast procedure was developed and validated for the determination of bisphenol A (BPA) in paper products using synchronous fluorescence spectroscopy. The method was used for the determination of BPA in thirteen types of paper products, including thermal receipt papers, lottery tickets, bus tickets, business cards, mailing envelopes, flyers, napkins, printing paper, food contact paper, kitchen rolls, toilet paper, newspapers, and magazines. BPA was found in 98% of thermal receipt papers (n = 341) at concentrations ranging from below the limit of quantification (LOQ) to 27.7 mg g−1 with a geometric mean of 14.6 mg g−1 and a median of 17.7 mg g−1. The detection rate for other paper products was 96%, with BPA concentrations ranging from below the LOQ to 379 µg g−1 and a median of 17.3 µg g−1. The estimated daily intake for the adjusted bodyweight of BPA (calculated at median concentrations) through dermal absorption from handling papers was 14.5 and 1070 ng day−1 for the general population and occupationally-exposed individuals, respectively. The proposed analytical method is simple, fast, and cost-effective for the determination of BPA in paper samples. Moreover, an estimated daily exposure of Brazilians to BPA through dermal absorption from handling different types of papers is shown.